When will the Germans Get Trapped in their Pension System? - Silke Uebelmesser; Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2001)
The upcoming demographic crisis in Germany demands fundamentalreforms of the pension system. In a democracy, reforms are, however, onlyfeasible when they are supported by the majority of the electorate. Todetermine whether the majority is in favor of reforms of the pension system,we calculate for each year the indifference age as the age of the cohortwhich is not affected by the reform and the median age as the age of thepolitically decisive cohort. Until 2023, the median age is below theindifference age implying that the young have the majority and the reformcan be democratically enforced. After 2023, Germany will be characterizedby a gerontocratic system where the old decide over the young. Only the fearthat the young might emigrate - and perhaps a certain altruistic attitudetowards their own descendants - will prevent the old from exploiting theyoung.
Keywords: 330; demographic crisis; pension reform; political feasibility; median age; indifference age